Seismic mitigation performance of shape memory alloy flexible circumferential joint in shield tunnel - Ma, Yongtao; Miao, Yu; Long, Xiaohong (Earthquake engineering & structural dynamics, 2023)
The circumferential joint of a shield tunnel is prone to damage under strong earthquakes, affecting the safety of the tunnel. This paper adopts an innovative shape memory alloy (SMA) flexible circumferential joint for longitudinal seismic mitigation of the tunnel. The SMA joint is composed of SMA ring springs and ordinary bolts. The SMA joint design is performed for a shield tunnel, and a simplified model of the SMA joint is proposed. Based on the generalised response displacement method, the longitudinal seismic mitigation analysis of the tunnel is conducted, the arrangement of SMA joints is discussed, and the seismic mitigation performance is evaluated. Results show that the SMA joint design method can efficiently complete the joint design, and the SMA joint model can accurately reflect the joint performance. SMA joints can reduce the stiffness of tunnel joints and have a good energy dissipation effect, which is suitable for shield tunnel seismic mitigation. An appropriate SMA joint arrangement can concentrate the tunnel joint deformation and effectively reduce the opening width between the tunnel segment rings. It can also dissipate energy and reduce the internal force of the tunnel joint, thus enhancing the seismic safety of the tunnel.